Factors Affecting the Variation in Sexual Activity and Response before and During Pregnancy among Pregnant Women in Rasht City, Northern Iran - Alizadeh, Shiva; Riazi, hedyeh; Alavi Majd, Hamid; Alavi Majd, Hamid; Ozgoli, Giti (Galen Medical Journal, 2019)
Background: Pregnancy is one of the most sensitive periods in a woman’s life, which sexual activity and intercourse are affected by the variations in physical, hormonal, and mental conditions. This study aimed to investigate the factors affecting the variations in sexual response before and during pregnancy. Materials and Methods: This cross-sectional study was conducted on pregnant women at Rasht city (northern Iran), 2018. The data were collected using the pregnancy sexual response inventory (PSRI). Statistical analysis was performed using descriptive and inferential tests by SPSS 25 at a significance level of P<0.05. Results: The mean total score of sexual activity and response of the subjects before and during pregnancy were 73.04 ± 14.81 and 46.88 ± 16.51, respectively. The variations in the total score of sexual activity and response during pregnancy decreased by 26.16 points during pregnancy compared to before pregnancy. There was a positive correlation between the number of children and the score of the variations in sexual activity and response before and during pregnancy (r=0.143). Conclusion: Couples with a higher level of education and a lower number of children had fewer variations in their sexual response. Therefore, it is possible to enhance the couples’ sexual health through encouraging them to appropriately plan for childbearing, to share the responsibilities of taking care of their children, and to continue their education at higher levels. [GMJ.2019;8:e1531]